Frontal Fibrosing Alopecia and Lichen Planopilaris: Clinical, Dermoscopic and Histological Comparison. (January 2013) - Rossi, A.; Iorio, A.; Scali, E.; Gerardi, M.; Priolo, L.; Misciali, C.; Carlesimo, M.; Calvieri, S.; Mari, E.
Frontal fibrosing alopecia (FFA) and lichen planopilaris (LPP) are classified as scarring alopecia. Most authors consider FFA as a clinical variant of LPP on the basis of their similar histological findings; other authors think these pathologies are two different entities. We studied 48 cases of FFA and 86 cases of LPP. Clinical diagnosis was histologically confirmed and all patients underwent videodermoscopy. Moreover, histological study, identifying the main targets of these diseases, results helpful to confirm the diagnosis. FFA selectively affects vellus-like hair in the frontoparietal region and is characterized by a mild skin atrophy and a total loss of follicular openings. In LPP an involvement of total preterminal, terminal and vellus-like follicles, partial or total loss of follicular openings, diffuse hair thinning and twisting, perifollicular erythematous or violaceous papules and mild/severe spinous follicular hyperkeratosis with scalp sclerosis are the features observed. Videodermoscopy improves diagnostic capability, appearing to be helpful to underline FFA and LPP features, confirmed by histologic studies which identify and show different intensity of inflammatory process. Therefore, the two diseases could be considered two different entities on the basis of the different clinical features and the different targets, that can be related to a different pathogenetic mechanism.